The global pandemic and changes in women's reproductive health: an observational study - Haile, Liya; Van De Roemer, Niels; Gemzell-Danielsson, Kristina; Perello Capo, Josep; Lete Lasa, Inaki; Vannuccini, Silvia; Koch, Martin C.; Hildebrandt, Thomas; Calaf, Joaquim (European Journal of Contraception and Reproductive Health Care, 2022)
Objective The COVID-19 global pandemic has led to the death of millions around the world and impacted the overall health of many people. In this article we aim to compare reproductive health indicators in the first 6 months of 2020 to the prior year, as well as explore stress and quality of life during this time. Methods This retrospective observational study examined the menstrual cycles of 1159 women who were using a fertility tracking device to record their menstrual cycle and BBT data. We utilised a supplemental mobile application to administer a supplemental survey to collect data on stress and quality of life. Descriptive analyses were conducted with t-tests for two-group comparisons. Results Study participants from 15 countries contributed to a total of 13,194 cycles. 23.1% (268/1159) responded to the survey focussed on assessing psychosocial distress. 44.4% (119/268) of the study participants reported that they had noticed a change in their menstrual cycle, temperature curve, or menstruation in the past 12 months. Cycle analysis found the average cycle length and pre-ovulation phase length was longer in the first 6 months of 2019, while the average days of menstruation was slightly longer in 2020. Discussion Our findings indicate that menstrual cycle indicators changed only slightly in the first 6 months of 2020 but were still statistically significant. We were also able to understand that these study participants had some level of awareness of changes to their menstrual health.
CRIS-Team WoS Importer:2022-02-04